What We See as One River is a Convergence of Many: Three Convergence Commitments in University Teaching - Grain, Kari (Journal of Contemporary Issues in Education)

(untitled) (University of Alberta, 2023)
Michael Marker knew we are never just one thing. He often wrote about concepts that gesture toward convergence: To converge as a way of blurring boundaries; To converge as a challenging process of coming-together; to converge educationally in a murky, “alluvial” place of relationality that is only navigable through artistic and storied methodologies (Marker, 2017). Marker steadfastly resisted colonial structures that attempted to tidily delineate knowledge and compartmentalize the unknowable. In this article, I reflect upon Marker’s scholarship through the idea of convergence, and I outline three conceptual spaces of convergence that I have observed in his work. Through analysis of Marker’s body of work, and an attunement to his loving and poetic forms of resistance, I articulate my commitments in my role as a relatively new, non-Indigenous faculty member in his former department at the University of British Columbia. I think of convergence commitments as relational meeting places that can be at once joyful and also tension laden; they are necessary practices that help me to decentre and “muddify” Western ways of knowing that I have been socialized to enact in institutional spaces.